SCARE: When Economics Meets Epidemiology with Covid-19 - André de Palma; Nathalie Picard; Stef Proost (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We develop an epidemic model to explain and predict the dynamics of the SARS-CoV-2 virus and to assess the economic costs of lockdown scenarios. The standard epidemic three-variable model, SIR (Susceptible, Infected and Removed) is extended into a five-variable model SCARE: Susceptible, Carrier, Affected (i.e. sick), Recovered and Eliminated (i.e. dead). Using WHO and Oxford data on cases and deaths, we rely on indirect inference techniques to estimate the parameters of SIR and SCARE. We consider different observation rates and stringencies of lockdown. Both models are estimated for five countries and provide predictions on the number of cases, the number of deaths, and the basic reproduction number, R0. SCARE is used to test the impact of lockdown policies on economic costs for the well-documented Belgium case. Economic assessments of epidemic results on hospital, morbidity and mortality together with macro-economic impacts show that the total net benefits of the Belgian lockdown policy is negative for low valuations of life years lost. The gains of extending the Belgian lockdown policy are negative even for high valuation of life.
Keywords: 330; COVID-19; public health; policy; simulation; social contact